GE_GERICHTE P/19443/2022 vom 18. Oktober 2023 - GE Cour de justice (2023)
SÉQUESTRE(MESURE PROVISIONNELLE);MANDAT DE PERQUISITION;SCELLÉS;TÉLÉPHONE MOBILE;CONDITION DE RECEVABILITÉ;RETARD | CPP.263; CPP.393.al1.leta; CPP.396; CPP.339.al2.letd